Strategi Membendung Islamofobia melalui Penguatan Kurikulum Perguruan Tinggi Berwawasan Islam Aswaja Annahdliyah - Ibda, Hamidulloh (Universitas Islam Negeri Raden Intan Lampung, 2018)
This article discusses the dynamics of Islamophobia and strategies to stem it. This study uses a descriptive qualitative approach that focuses on review Islamophobia and the strategy STAINU Temanggung to stem it through strengthening the curriculum. The results of this study, Islamophobia is a fear of everything that smells of Islam and Muslims. Islamophobia is not a product of Islam, because is caused propaganda, political interests, the influence of the mass media, hatred, Western fears of Islam, and a partial understanding of Islam. The strategy of STAINU Temanggung stemmed Islamophobia through strengthening the KKNI-SNPT curriculum based on Aswaja Annahdliyah in the dimensions of the Tri Dharma of Universities. All aspects of education-teaching, research, and community service are directed towards building competency, character, and values of Aswaja Annahdliyah, moderation, and values of mabadi khaira ummah. Through this strengthening, the face of Islam appears moderate, tolerant, friendly, and not radical, which in the long run stemming Islamophobia, especially in plural areas automatically.